Integration of Islamic Values and Malay Culture in the Development of Halal Tourism Destinations in South Lampung - Khoirul Umam Addzaky; Muhammad Mustofa; Andieni Putri Olivia Arifin (Research Synergy Foundation, 2024)
The development of halal tourism encounters the challenge of harmonizing Islamic values with local cultural traditions, ensuring that the authenticity of both is preserved and respected. This phenomenon is seen in South Lampung, where there is an urgent need to develop a halal tourism model that is harmonious with the local Malay culture. This study aims to analyze the process of integration of Islamic values and Malay culture in the development of halal tourism, identify the characteristics of culture-based halal tourism destinations, and formulate strategies to optimize the development of halal tourism in South Lampung. Through an ethnographic approach with in-depth observation, interviews and documentation analysis in three main destinations: Muara Indah Beach, Pasir Putih Beach, and Dermaga Bom Culinary Tourism. The results revealed a unique integration model based on the philosophy of “Piil Pesenggiri” which was successfully harmonized with sharia principles in the development of tourist destinations. This model is manifested in the implementation of “Islamic hospitality” that blends with the value of “Nemui Nyimah”, adaptation of traditional performing arts according to sharia standards, and preservation of local culinary through halal certification. These findings challenge the conventional paradigm that positions the modernization of halal tourism and the preservation of traditional culture as a dichotomy.